The impact of earnings per share, dividend per share and book value per share against stock price evidence from FBM KLCI / Nur Sofie Baizurin Beddu - Beddu, Nur Sofie Baizurin (2015)
A number of studies have been undertaken to identify the factors that affect stock price. The present study examined the impact of earnings per share, dividend per share and book value per share on stock price on a sample of 37 companies listed in the main board of Kuala Lumpur Composite Index (KLC1) from the year 2009 until 2014. The results reveals that earnings per share, dividend per share and book value per share had insignificant impact on the stock price in the KLCI.